2005
DOI: 10.1557/jmr.2005.0258
|View full text |Cite
|
Sign up to set email alerts
|

Nanoindentation Analysis of Mechanical Properties of Low to Ultralow Dielectric Constant SiCOH Films

Abstract: Carbon-doped oxide SiCOH films with low to ultralow dielectric constants were prepared on a Si substrate by plasma-enhanced chemical vapor deposition (PECVD) from mixtures of SiCOH precursors with organic materials. The films have different levels of nanoscale porosity resulting in different dielectric constants and mechanical properties. The mechanical properties of the films have been characterized by continuous-stiffness nanoindentation measurements. To study the effect of film thickness, each group of samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Researchers at Motorola [43] have concluded that passing the CMP process of low-k material is not a simple factor of modulus, hardness, adhesion or toughness, but a combination of all of these properties. As stated before, the mechanical properties of low-k films depends on chemical structure, amount of porosity and composition, Elastic modulus and hardness values of the different dielectric thin films varies from 2 to 14 GPa and 0.5 to 7 GPa respectively [41][42][43][44][45]. Volinsky et al [1] have found a linear relationship between hardness and elastic modulus for silicate low-k dielectric films in nanoindentation testing with continuous stiffness measurement (CSM) attachment.…”
Section: Mechanical Characterization Of Low-k Structures By Using Nanmentioning
confidence: 99%
See 3 more Smart Citations
“…Researchers at Motorola [43] have concluded that passing the CMP process of low-k material is not a simple factor of modulus, hardness, adhesion or toughness, but a combination of all of these properties. As stated before, the mechanical properties of low-k films depends on chemical structure, amount of porosity and composition, Elastic modulus and hardness values of the different dielectric thin films varies from 2 to 14 GPa and 0.5 to 7 GPa respectively [41][42][43][44][45]. Volinsky et al [1] have found a linear relationship between hardness and elastic modulus for silicate low-k dielectric films in nanoindentation testing with continuous stiffness measurement (CSM) attachment.…”
Section: Mechanical Characterization Of Low-k Structures By Using Nanmentioning
confidence: 99%
“…6, where cracks are indicated by arrows on the micrographs. Many researchers have observed this kind of fracture behavior (pop-in event) in various types of low-k materials, bulk glasses and silica foams [42][43][44][45][46] Table 5 gives the information about the BD films fracture/delamination during nanoindentation testing, in terms of threshold load, threshold indentation depth and % of thickness at which film cracking occurs. For 100 nm thick film, failure is observed when the indenter tip is in the substrate and it can be seen in Fig.…”
Section: Mechanical Characterization Of Bd Thin Films With Varying Thmentioning
confidence: 99%
See 2 more Smart Citations
“…The amphiphilic triblock copolymers act as porogen and are evaporated upon thermal or UV curing, leaving a porous silica network connected to alkyl groups as part of the network or terminal bonds. On the other hand, the CVD-OSG films 7,8 are used as reference materials to compare the elastic modulus values of several OSG materials with different pore topologies quantitatively.…”
Section: Introductionmentioning
confidence: 99%